PENGGUNAAN MEDIA PAPAN DART UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA - Azhari, Biantica Rena; Hanifah, Nur; Gusrayani, Diah (Jurnal Pena Ilmiah, 2017)
During earlier data observation on the study of Social Sciences, some problems faced by students are found, that is teacher’s lack of learning media that results in student’s lack of motivation in learning and low achievement. Based on the problem found, the use of Dart Board Media is Applied. The0purpose0of0this0research is0to0find planning, process, and increase of students’ motivation and achievement. On the first term, students motivation achieve 91,92%, on second term 96,89% and 100% on the third term. For the learning achievement 34,79% on the first term, 60,86% on the second term and 86,95% on the third term. From the shown data results we can conclude that the use of dart board media can increase students’ motivation and learning achievement on learning the material Kinds of Businesses and Economical Activities in Indonesia.